The Effectiveness of Ict in Edifying Language Learning: a Quasi -Experimental Study - S, Mohankumar; V.Vijayalakshmi, Dr; C B, Manjusha (International Journal of Engineering and Technology, 2018)
Technological development is bringing in tremendous changes in almost all the arenas. Educational needs of today are not like those days where traditional practices served the purposes. ICT and e-learning is replacing the educational systems. In such a scenario, students are to be aware of the better platforms to equip themselves with the recent trends and changes. The objective of this research paper is to enthrove how effective will be the process of learning if ICT is implemented in the classrooms. Activities based on ICT focusing on enhancing writing skill are the core of this research paper.Â Â